308. RIGHT TOP PULMONARY VEIN IS A VENOUS ANOMALY OF WHICH SURGEONS SHOULD BE AWARE IN SUBCARINAL DISSECTION FOR RADICAL ESOPHAGECTOMY. (24th September 2022) - Sato, Yuta; Tanaka, Yoshihiro; Ohno, Shinya; Endo, Masahide; Yoshida, Kazuhiro
Abstract: A right top pulmonary vein (RTPV) that crosses behind the right bronchus, is a variation of the superior posterior pulmonary vein in the right upper lobe. Damage of this vessel can lead to intraoperative bleeding, congestion of the posterior segment of the right upper lobe, and cardiac tamponade. Subcarinal lymph node dissection is mandatory in radical esophagectomy for esophageal cancer, and the RTPV is an anomalous vessel of which surgeons should be aware. A 70-year-old man underwent thoracoscopic esophagectomy for esophageal cancer (T3N1M0). An anomaly of the superior posterior pulmonary vein in the right lobe was recognized on preoperative computed tomography imaging. With simulation and intraoperative navigation using three-dimensional imaging (SYNAPSE VINCENT, Fuji Photo Film Co., Ltd, Tokyo, Japan) of the same view as that observed during the operation, radical subcarinal dissection could be performed with preservation of the RTPV. Only 5 case reports have described the association of RTPV in esophagectomy. In review of the literature, the incidence of RTPV ranged from 0.28 to 9.3%, and its mean vascular diameter ranged from 7.0 mm to 2.2 mm, with the right superior pulmonary vein being a common inflow site. Our case in which the RTPV ran dorsal to the right main bronchus is very rare. In radical subcarinal dissection of esophagectomy in cases with RTPV, it is important to recognize the posterior pericardial plane and release the ventral fixation of these lymph nodes to free space for the back side. Based on our review of the relevant literature, an RTPV larger than 4.5 mm should be noted in order to prevent injury and ligation should be avoided. The preoperative recognition of this abnormal vessel using 3D imaging was very useful for radical SCLN dissection during thoracoscopic esophagectomy.